OXA-244-Producing ST131 Escherichia coli From Surface and Groundwaters of Pavia Urban Area (Po Plain, Northern Italy) - AbuAlshaar, Aseel; Piazza, Aurora; Mercato, Alessandra; Marchesini, Federica; Mattioni Marchetti, Vittoria; Bitar, Ibrahim; Hrabak, Jaroslav; Spalla, Melissa; Pilla, Giorgio; Sconfietti, Renato; Migliavacca, Roberta (Frontiers in microbiology, 2022)
The study aimed to investigate (i) the occurrence of third-generation cephalosporins and/or carbapenems non-sensitive Enterobacterales in Pavia surface and groundwaters, (ii) their resistance determinants, and (iii) the clonal features of the most relevant strains. During May 13 and 14, 2019, n = 18 water samples from n = 12 sampling sites in the urban/peri-urban area of Pavia (Po Plain, Northern Italy) have been evaluated. At first, hydrochemical analysis and bacterial plate counts were carried out on all the water samples. One milliliter of each water sample was then screened on both MacConkey agar (MC) added with cefotaxime (1 mg/L; 2 mg/L) and MC plus meropenem (0.25 mg/L; 4 mg/L). Species identification and antimicrobial susceptibilities were assessed by MicroScan autoSCAN-4. Double Disk Synergy (DD) test, CT103XL microarray, acc(6')-Ib-cr, qnrS, blaCTX-M-/MOX-/VEB-/OXA-type genes targeted PCR and sequencing, Pulsed-Field Gel Electrophoresis (PFGE), MultiLocus Sequence Typing (MLST), and Whole-Genome Sequencing on selected strains were performed. A total of n = 30 isolates grown on β-lactams enriched MC: Escherichia coli (n = 21; 70%), Klebsiella spp. (n = 5; 16.6%), Citrobacter freundii (n = 2; 6.7%), and Kluyvera intermedia (n = 2; 6.7%). All E. coli and K. pneumoniae were ESβL-producers by DD. The 66.6, 38.0, and 19.0% of E. coli were ciprofloxacin/levofloxacin, trimethoprim-sulfamethoxazole, and gentamicin resistant (EUCAST 2019 breakpoints), respectively. A blaCTX-M-type determinant was identified in E. coli (n = 20/21; 95.2%) and K. pneumoniae (n = 2/3; 66.7%). The remaining E. coli was blaVEB-1 and blaMOX-2 genes positive. The aac(6')-Ib-cr determinant was found in n = 7 E. coli and n = 1 K. pneumoniae, while qnrS was found in n = 1 E. coli and n = 2 K. pneumoniae. PFGE showed clonal heterogeneity among ESβL-E. coli. Two out of four E. coli detected as blaOXA-244-positive, belonged to the pandemic ST131. One XDR K. pneumoniae from a stream sample, detected as blaKPC-2 positive, resulted of ST258. The epidemiological impact of blaOXA-244 ST131 E. coli and blaKPC-2 ST258 K. pneumoniae presence in surface waters of an urban area in Northern Italy must not be underestimated.
Keywords: ST131 Escherichia coli; Enterobacterales; Italy; OXA-244; ESβLs; ST258 Klebsiella pneumoniae; carbapenemases; river and ground waters